2009
DOI: 10.1007/s11431-009-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Wide band modeling of large power transformer windings for very fast transient overvoltage (VFTO) analysis

Abstract: Citation: Yang Y, Wang Z J. Wide band modeling of large power transformer windings for very fast transient overvoltage (VFTO) analysis.There are some difficulties in using multi-transmission-line (MTL) model for wide band modeling of whole windings of the large power transformer. In this paper, the normalized MTL model is firstly derived, with which not only the difficulty of modeling windings with different turn-lengths using MTL can be solved, but also the model can be extended to the modeling of the multi-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Substitute it into (16), and then elimination , we can obtain (17) It is shown that the attenuation factor is determined by , representing the dielectric loss and representing the resistance loss. Then, we can define the specific form of and as follows.…”
Section: B Fitting Formula Of Attenuation Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitute it into (16), and then elimination , we can obtain (17) It is shown that the attenuation factor is determined by , representing the dielectric loss and representing the resistance loss. Then, we can define the specific form of and as follows.…”
Section: B Fitting Formula Of Attenuation Factorsmentioning
confidence: 99%
“…Power transformers and other large electrical devices are vulnerable to the very fast transient overvoltage (VFTO) generated by the switching operations of vacuum circuit breakers in adjacent gas-insulated substations (GIS). Extremely nonuniform transient voltage distribution which could cause great harm to the insulation system might appear Many achievements have been published about the related modeling and computational methods [5]- [17]. However, there is still no effective method taking the transformer loss into consideration and only a few publications about determining the impact of frequency-dependent loss on the voltage distribution calculation in fast transient frequency range (within tens of megahertz).…”
Section: Introductionmentioning
confidence: 99%
“…Transformers are the most important equipment in the power station, whose damage could lead to serious consequences [1][2][3][4]. At present, there are many accidents occurred in the substation equipment, which contains a large number of unidentified insulation accident.…”
Section: Introductionmentioning
confidence: 99%
“…By means of the computer simulation tools to predict distribution of transient voltage in transformer winding is a major method to guide the insulation structure design with lots of papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] published. However, there are only scarce publications about the loss characteristics of the power transformers at the fast transient frequency range (about a few megahertz to tens of megahertz).…”
Section: Introductionmentioning
confidence: 99%